(untitled) (IJOVTECH, 2026)
Digital marketing is becoming increasingly popular in Nigeria, mainly due to the rapid development of new technologies related to the Internet. Concerns about security, privacy, data leak, and trust have affected consumers' unbridled enthusiasm for the digital marketplace. Consumers are becoming increasingly aware of the presence of digital manipulations. Thus, the present study examines the effect of digital distrust on attitudes toward digital marketing among civil servants. Two hundred and twenty-eight employees of the Ebonyi state government were sampled from different ministries, departments, and agencies. The respondents completed a self-report measure of digital distrust and attitude towards digital marketing. The simple regression analysis revealed that digital distrust positively predicts digital marketing. The implications of the study are discussed.